DILEMA PENERAPAN PERATURAN DAERAH (PERDA) SYARI’AH DI INDONESIA - Valid Fathony, Bimba (JISIPOL | Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
Regional Regulations are an important element in the legal view of legislation. The implementation of Regional Regulations based on Sharia not only creates pros and cons in society, but also raises very significant constitutional problems. This article aims to describe the Dilemma of the Implementation of Sharia Regional Regulations in Indonesia. This study uses a qualitative research method using a descriptive approach. This research is a type of library research. In this study, it is concluded that Sharia Regional Regulations must not conflict with higher regulations and must pay attention to the interests of the community and comply with national legal principles. The existence of Sharia Regional Regulations in Indonesia is a reflection of the dynamics of local democracy and the plurality of society. The implementation of this Sharia Regional Regulation raises a dilemma where, for some people, Sharia Regional Regulations are expected to be an effort to find a way out of various problems currently facing the nation, on the other hand, Sharia Regional Regulations are also feared to be a tool for religious political interests. Sharia Regional Regulations are often viewed as unconstitutional because religious affairs are the authority of the central government, not the regions.